Northwest Art Today : Adventures in Art. - Reed, Gervais; Rogers, Millard B. (Seattle : Seattle World's Fair, 1962)
Alps, Glen E. ; Anderson, Frederick ; Anderson, Guy ; Arneson, Robert ; Aspell, Peter ; Balazs, Harold R. ; Banks, Virginia ; Benjamin, Max ; Brazeau, Wendell ; Bunce, Louis ; Callahan, Kenneth ; Caplan, Irwin ; Colescott, Robert ; Corley, Ward ; Cumming, William ; Elshin, Jacob ; Erickson, John ; Feasley, Robert ; Gabel, Marlene ; Gardner, Byron ; Gemberling, Kathleen ; Gerald, James Fitz ; Gonzales, Boyer ; Graves, Morris ; Hafermehl, Louis C. ; Hales, James H. ; Haley, Sally ; Hall, Carl ; Hansen, Gaylen C. ; Hansen, James Lee ; Hardy, Tom ; Heany, Charles ; Heidel, Frederick ; Heyser, Norma ; Hill, Ray ; Hixson, William J. ; Hofmeister, Andrew L. ; Horiuchi, Paul ; Howard, Robert B. ; Hultberg, Paul ; Isaacs, Walter ; Ivey, William ; Izquierdo, Manuel ; Jameson, Demetrios G. ; Jarvis, Donald ; Jensen, Ray ; Kelly, Lee ; Kingsbury, Ragnihild ; Korner, John ; Kowert, Hank ; Krause, Laverne ; Laisner, George Alois ; Littman, Frederic ; Mair, William J. ; Mason, Alden C. ; Mason, John ; Matsudaira, John ; McCosh, David J. ; McCracken, Philip ; McLarty, Jack ; Meitzler, Neil ; Monaghan, Keith ; Morris, Carl ; Morris, Hilda ; Moseley, Spencer A. ; Ng, Win ; Nicholson, Patricia K. ; Okada, Frank S. ; Onley, Toni ; Patterson, Ambrose ; Patterson, Viola ; Peel, Donald ; Pehr ; Pen, Everett Du ; Piladakis, Emanuel ; Reynal, Jeanne ; Russo, Michele ; Shadbolt, John L. ; Siebner, Herbert ; Smith, Charles W. ; Smith, Gordon ; Stangl, Jack ; Takemoto, Henry ; Tanabe, Tako ; Tawney, Lenore ; Taysom, Wayne P. ; Tobey, Mark ; Tomkins, Margaret ; Tsutakawa, George ; Utley, Windsor ; Voulkos, Peter ; Wahl, Harold ; Washington, James W. ; Welman, Val ; Wilson, Milton ; Zaloudek, Duane
biog. per kunstenaar
Engels
Nortwest Art Today : Adventures in Art, World's Fair Seattle, 21.04 - 21.10.1962
boek
Keywords: Amerika; Seattle